PENDAMPINGAN DAN PEMBERDAYAAN MASYARAKAT SEBAGAI TUTOR BACA TULIS AL-QUR’AN DENGAN MEDIA FLASHCARD PADA SISWA ERA COVID-19 DI DUSUN MARON DESA GENTENG KULON - Yuli Tri Andini; Riris Wahyuningsih (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
The activity of mentoring students by students in studying in Maron Hamlet is a form of community service. This activity was carried out to overcome the obstacles of parents in terms of learning assistance, especially during the Covid-19 pandemic situation. Constraints faced include the inability of parents to accompany learning due to the low level of parental education, busy parents who mostly work as traders and grocery store businesses in Maron RTH, and the inability of parents to understand technology. Service activities carried out in learning to students are carried out using the PAR (Participatory, Action, Research) approach. The purpose of this service activity is to provide assistance to students in reading and writing the Qur'an with interesting learning techniques, one of which is using flashcard media through facilitators in the form of empowering local communities as tutors so that the service programs carried out are carried out in a sustainable manner. So that the results of the service to be achieved in this service activity can be carried out properly, and can provide benefits for students and the local environment on an ongoing basis.